2008
DOI: 10.1242/jeb.010652
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional flow structures and evolution of the leading-edge vortices on a flapping wing

Abstract: SUMMARYFollowing the identification and confirmation of the substructures of the leading-edge vortex (LEV) system on flapping wings, it is apparent that the actual LEV structures could be more complex than had been estimated in previous investigations. In this experimental study, we reveal for the first time the detailed three-dimensional (3-D) flow structures and evolution of the LEVs on a flapping wing in the hovering condition at high Reynolds number (Re=1624). This was accomplished by utilizing an electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 43 publications
(115 reference statements)
6
46
1
Order By: Relevance
“…At least in bats, these vortices were connected with spanwise vortices shed as a result of changes in circulation about the wing throughout the wingbeat [11]. When lowering the iso-value of the Q-criteria in our plots, which is used to identify vortices [35], we also find these spiralling vortices to be connected to spanwise vortices, which is in agreement with findings for bats [11]. This is consistent with a continuous change in bound circulation found during the wingbeat in birds [51].…”
Section: Wakesmentioning
confidence: 95%
“…At least in bats, these vortices were connected with spanwise vortices shed as a result of changes in circulation about the wing throughout the wingbeat [11]. When lowering the iso-value of the Q-criteria in our plots, which is used to identify vortices [35], we also find these spiralling vortices to be connected to spanwise vortices, which is in agreement with findings for bats [11]. This is consistent with a continuous change in bound circulation found during the wingbeat in birds [51].…”
Section: Wakesmentioning
confidence: 95%
“…Two frame-straddling CCD cameras (PowerView Plus, 4008 3 2672 pixels) with lenses (Micro Nikkor 60 mm, Nikon, Japan) were used to capture the particle displacement. Asymmetric SPIV arrangement 43 was utilized, and the lenses and the cameras were mounted on an electromechanical translation apparatus to satisfy the Scheimpflug condition, which requires the measurement, image, and lens principle planes to intersect at a common point, as shown in Figure 1.…”
Section: Spiv Techniquementioning
confidence: 99%
“…Lu and Shen (Lu and Shen, 2008) studied experimentally the 3D flow structures and evolution of the LEV on a flapping wing in the hovering condition. Their results showed that the LEV system is a collection of four vortical elements: one primary vortex and three minor vortices.…”
Section: Introductionmentioning
confidence: 99%